PELAKSANAAN PROGRAM KAMPUS MENGAJAR DALAM MENINGKATKAN LITERASI DAN NUMERASI PESERTA DIDIK DI SD NEGERI 1 DODOGAN - Nugraha, Adi; Rigianti, Henry Aditia (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2024)
One of the causes of low literacy and numeracy skills among students is the lack of motivation to learn, insufficient supporting facilities, inadequate school libraries and reading materials, and a lack of in-depth guidance for students who are behind in class. To address this, the Indonesian government, through the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), has provided opportunities for university students to act as agents of change in improving literacy and numeracy skills in schools. This research was conducted at SD Negeri 1 Dodogan, Jatimulyo Village, Dlingo District, Bantul Regency, Special Region of Yogyakarta. This study employs a descriptive qualitative research method aimed at revealing events occurring in the field based on actual facts. The qualitative method is often used to study subjects according to real conditions in the field. The researcher collected data using unstructured interviews, observations, tests, and documentation. Based on the identified factors, the university students selected appropriate collaborative action plans to address the low literacy and numeracy skills among students. The campus teaching program successfully improved students' literacy and numeracy skills significantly. The average literacy pre-test and post-test scores increased from 63.2% to 72.1%. Meanwhile, the average numeracy pre-test and post-test scores rose from 47.3% to 80.3%. This improvement in fifth-grade AKM scores aligned with an increase in students' motivation to learn.